2016
DOI: 10.1038/nature18909
|View full text |Cite
|
Sign up to set email alerts
|

An aqueous, polymer-based redox-flow battery using non-corrosive, safe, and low-cost materials

Abstract: Electricity users expect energy on demand. This poses a problem for renewables, such as solar, wind or hydroelectric, as the supply is naturally intermittent. Building scalable and inexpensive energy storage is the answer, and here we describe a new rechargeable battery system that uses salt solutions of organic polymers and a cheap filter membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 3 publications
2
133
1
Order By: Relevance
“…5,6 Further disadvantages of classical RFBs are the deficient civil and environmental standards associated with ore mining, the applied hazardous and highly corrosive acidic electrolytes, and the expensive membranes such as the commonly used Nafion (DuPont, Wilmington, DE, USA) cation-exchange membrane. [6][7][8][9][10] The development of an all-organic RFB with inexpensive and sustainable redox-active materials and low-cost membranes may overcome these drawbacks. 7,[10][11][12][13][14] Among others, Darling et al 15 conducted cost analyses, which revealed that the price of the active material itself and the membrane represent the main costs of these systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Further disadvantages of classical RFBs are the deficient civil and environmental standards associated with ore mining, the applied hazardous and highly corrosive acidic electrolytes, and the expensive membranes such as the commonly used Nafion (DuPont, Wilmington, DE, USA) cation-exchange membrane. [6][7][8][9][10] The development of an all-organic RFB with inexpensive and sustainable redox-active materials and low-cost membranes may overcome these drawbacks. 7,[10][11][12][13][14] Among others, Darling et al 15 conducted cost analyses, which revealed that the price of the active material itself and the membrane represent the main costs of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] The development of an all-organic RFB with inexpensive and sustainable redox-active materials and low-cost membranes may overcome these drawbacks. 7,[10][11][12][13][14] Among others, Darling et al 15 conducted cost analyses, which revealed that the price of the active material itself and the membrane represent the main costs of these systems. Cost-efficient organic charge-storage materials can feature a price advantage compared with metal-based RFBs; in particular, if the raw materials are affordable, no synthesis or fewer synthesis procedures are required and the avoidance of elaborate purification steps can be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Whereas previous studies have used such membranes to prevent electrolyte mixing, this work investigates battery operation using mixed electrolytes in order to simplify the battery hardware and to reduce capital costs. As with the all-iron flow battery, moderate amounts of electrolyte crossover in this configuration would not cause irreversible performance loss.…”
mentioning
confidence: 99%
“…These organic molecules can be tailored to have certain properties, such as fast kinetics, high solubility and high associated cell voltage in the resulting flow battery [25][26][27][28]. They typically dissolve in either aqueous or non-aqueous electrolytes and can be incorporated in polymers [29] or appear as solid electrodes mixed with porous carbon and binders [30].…”
Section: Figurementioning
confidence: 99%